An analysis of different Brexit outcomes and their effect on inward FDI to the UK. (2019) - Head, Jeremy
In June 2016, the UK voted to leave the EU, and the economic implications of 'Brexit' are starting to take on a clearer focus. This paper seeks to outline the patterns of inward FDI to the UK. The paper analyses the possible impacts of different Brexit scenarios on inward FDI to the UK. The paper's key arguments include that 'harder' forms of Brexit are likely to have worse outcomes in terms of inward FDI to the UK, with export platform FDI potentially significantly affected. The effects of Brexit could also be diverse in different industries, given the different motives for FDI, and also diverse in terms of the type of activity of the FDI. Moreover, given the patterns of FDI in the UK, the regional impacts of Brexit will not be evenly spread. The findings have clear policy implications surrounding the Brexit negotiation process.